Development and validation of a food pyramid for Swiss athletes - Mettler, S.; Mannhart, C.; Colombani, P. C. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
Food-guide pyramids help translate nutrient goals into a visual representation of suggested food intake on a population level. No such guidance system has ever been specifically designed for athletes. Therefore, the authors developed a Food Pyramid for Swiss Athletes that illustrates the number of servings per food group needed in relation to the training volume of an athlete. As a first step, an average energy expenditure of 0.1 kcal/kg/min for exercise was defined, which then was translated into servings of different food groups per hour of exercise per day. Variable serving sizes were defined for athletes` different body-mass categories. The pyramid was validated by designing 168 daily meal plans according to the recommendations of the pyramid for male and female athletes of different body-mass categories and training volumes of up to 4 hr/d. The energy intake of the meal plans met the calculated reference energy requirement by 97% ± 9%. The carbohydrate and protein intakes were linearly graded from 4.6 ± 0.6-8.5 ± 0.8 g/kg/d and 1.6 ± 0.2-1.9 ± 0.2 g/kg/d, respectively, for training volumes of 1-4 hr of exercise per day. The average micronutrient intake depended particularly on the dietary energy intake level but was well above the dietary reference intake values for most micronutrients. No tolerable upper intake level was exceeded for any micronutrient. Therefore, this Food Pyramid for Swiss Athletes may be used as a new tool in sports nutrition education (e.g., teaching and counseling).